(untitled) (Journal of actual problems of jurisprudence, 2018)
The article comprehensively report the status of the state language as it stated in the message of the President NursultanNazarbaev`s,Kazakhstan’s Way 2050: «The overall goa», «common interest», «common future» and is determined by its role in the production process of the criminal case Appreciation is given to decisions (fatwa announcement, coming to an amicable agreement) both to oratorical words and reasonable opinions fair and wise biy`s of the Kazakh society in the course of settlement of disputes. Key words: Society, state, tradition, culture, national language, biy, law enforcement agencies, the decision, the dispute, the legal culture.